Sosialisasi Pendidikan Karakter Anak dengan Media Kartun Bocah Hutan Mowglu dan Goldilocks di KB Ceria Kartasura Sukoharjo Jawa Tengah - Nurul Ilmi Azizah, Annafi; Cholisa Nadhifa, Avida; Lailatul Rohimah, Qori; Mutmainah, Fitri; Harnanto, Tantrianti; Shohwah, Izzathush; Melia Tamsir, Jenny; Durrotun Nafisah, Nona; Irma Fernanda, Dera (Seulanga: Jurnal Pengabdian Kepada Masyarakat, 2024)
Character education is an essential component in the development of early childhood, playing a role in shaping morals, social skills, and self-confidence. This community service aims to socialize character education through the media of the cartoon films " Bocah Hutan Mowgli dan Goldilocks " at KB Ceria, Kartasura, Sukoharjo. This program uses methods of exemplification, habituation, and storytelling by utilizing educational films as tools to instill moral values in children aged 3-4 years. The activity begins with a film screening, followed by an interactive discussion to understand the moral message in the story, as well as creative activities such as drawing and mimicking sounds. Evaluation was conducted through observation and Q&A to measure the improvement in vocabulary, story comprehension, and children's social-emotional skills. The results show that cartoon films are effective in capturing children's attention, strengthening literacy, and instilling positive character values such as courage, honesty, and responsibility. This program has a positive impact on building children's character through an engaging and age-appropriate approach. Further development with media variations and parental involvement is expected to expand the impact of this activity in the future.